Filtering methods to improve the accuracy of indoor positioning data for dairy cows. (May 2018) - Pastell, Matti; Frondelius, Lilli; Järvinen, Mikko; Backman, Juha
Abstract : Several indoor positioning systems for livestock buildings have been developed to be used as tools in automated animal welfare monitoring. In many environments the measurements from positioning systems still contain unwanted noise and the quality of the measurement data can be enhanced using filters. The aim of this study was to develop an efficient filter for positioning data measured from dairy cows with UWB-based indoor positioning system in a free stall barn. A heuristic jump filter combined with median filter and extended Kalman filter was developed and tested. The performance of the filters were compared against reference data collected from Insentec roughage intake feeders and scan sampling of animal presence in a specific lying stall with over 1500 reference observations from both methods. The quality of the positioning data was significantly improved using filtering. The 9th order median filter provided best estimates for cow position when the cows were not moving with median 100% of measurements located in correct stall and 84% in correct feeding trough when compared to the reference observations and measurements. The extended Kalman filter also improved the positioning accuracy significantly when compared to raw data and provides better of estimates of the trajectory of moving cows. Highlights: Heuristic jump filter removed large outliers from indoor positioning data. Extended Kalman filter achieved better results when tracking moving animals. High accuracy in measuring cow presence at feeding trough and stalls was achieved.